2021
DOI: 10.1186/s41983-021-00404-2
|View full text |Cite
|
Sign up to set email alerts
|

Does the second ischemic stroke herald a higher proportional risk for cognitive and physical impairment than the first-ever one?

Abstract: Background Post-stroke cognitive and physical disabilities are common sequelae; however, it seems that the second ischemic stroke carries a higher proportional risk more than expected. In this study, we aimed to study second stroke sequelae over first-ever one with regard to cognition and physical competence. This study was conducted on two groups; the first composed of 40 patients with acute first lifetime ischemic stroke, and the second group composed of 40 acute second lifetime ischemic stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The independent variables that were analyzed in the model were age, NIHSS, thrombolysis, thrombectomy, previous stroke, diabetes, atrial fibrillation, and prestroke independence. They were selected on the basis of prior literature and research 24–30 . To enhance the robustness of our analysis, we performed simple bootstrapping with 1000 samples and computed a 95% confidence interval (CI) using bias‐corrected and accelerated methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The independent variables that were analyzed in the model were age, NIHSS, thrombolysis, thrombectomy, previous stroke, diabetes, atrial fibrillation, and prestroke independence. They were selected on the basis of prior literature and research 24–30 . To enhance the robustness of our analysis, we performed simple bootstrapping with 1000 samples and computed a 95% confidence interval (CI) using bias‐corrected and accelerated methods.…”
Section: Methodsmentioning
confidence: 99%
“…They were selected on the basis of prior literature and research. [24][25][26][27][28][29][30] To enhance the robustness of our analysis, we performed simple bootstrapping with 1000 samples and computed a 95% confidence interval (CI) using bias-corrected and accelerated methods. The multicollinearity assumption was checked with the variance inflation factor (VIF), where a cutoff value of 2.5 was used.…”
Section: Ordinal Regressionmentioning
confidence: 99%
“…Patients who have had a stroke have a high risk of a recurrent stroke (Elwan et al, 2021). Repeat strokes ranged from 30-43% within 5 years.…”
Section: Frequency Of Attacksmentioning
confidence: 99%
“…In recurrent strokes, the disorders experienced will get worse -and increase the risk of disability and death (Oza et al, 2017). Research conducted by Elwan et al (2021) found that lesions which occur in recurrent stroke patients are more extensive than in patients experiencing their first stroke. The study concluded that patients experiencing a second stroke will have significant cognitive and physical disability compared to the first attack.…”
Section: Frequency Of Attacksmentioning
confidence: 99%